Preliminary Study on Reproductive Biology of the Abalone ( Haliotis varia ) at Phuket, Andaman Sea Coast of Thailand - Somchai Bussarawit; Preeda Kawinlertwathana; Anuwat Nateewathana (Agriculture and Natural Resources, 1990)
Reproductive biology of 214 individuals of abalone ( Haliotis varia ) was studied at Bon Island, Phuket in 1987. Mature gonads with apparently ripe eggs were found in January, March – April, June and August – October. Spawning, as indicated by gonad index and examination of ovaries, occurred in January – February, April – May, June – July, November – December. The smallest specimen with mature eggs measured was 17.3 mm. in length. Maximum fecundity was about 3.5 million eggs at the shell length of 41.8 mm. The sex ratio was not significantly different from 1 : 1 which respect to month and size class.